2v+18=6-4(v-17)

Simple and best practice solution for 2v+18=6-4(v-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2v+18=6-4(v-17) equation:


Simplifying
2v + 18 = 6 + -4(v + -17)

Reorder the terms:
18 + 2v = 6 + -4(v + -17)

Reorder the terms:
18 + 2v = 6 + -4(-17 + v)
18 + 2v = 6 + (-17 * -4 + v * -4)
18 + 2v = 6 + (68 + -4v)

Combine like terms: 6 + 68 = 74
18 + 2v = 74 + -4v

Solving
18 + 2v = 74 + -4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '4v' to each side of the equation.
18 + 2v + 4v = 74 + -4v + 4v

Combine like terms: 2v + 4v = 6v
18 + 6v = 74 + -4v + 4v

Combine like terms: -4v + 4v = 0
18 + 6v = 74 + 0
18 + 6v = 74

Add '-18' to each side of the equation.
18 + -18 + 6v = 74 + -18

Combine like terms: 18 + -18 = 0
0 + 6v = 74 + -18
6v = 74 + -18

Combine like terms: 74 + -18 = 56
6v = 56

Divide each side by '6'.
v = 9.333333333

Simplifying
v = 9.333333333

See similar equations:

| 19.5+0.5=10.6206-0.4t | | 24-5*3/8-5= | | -13=-4(4)+3 | | 5x+9=3z-1 | | -4+6(8X+2)=296 | | 121x^4-81=0 | | 7+2(6)= | | -3(9r+4)= | | .15w=45 | | Q+14=8q+7 | | -15=-4(3)+3 | | 3x^2-10+x=0 | | 64n^2+16n+1=0 | | 1x+2=2 | | -8m+-9(5+-3m)=12 | | -6X+2=-28X | | 3x^2-16-4=0 | | 8(x+7)=6x+74 | | 15x-10=x+4 | | 7s^2-2s-5=0 | | 14x+(3x+2)*(x-5)=0 | | 7z=2.1 | | 15r-18r=687 | | 5x+29=-7 | | 8(x+8)=6(x+80) | | 3--6/6+4= | | 11=-4(2)+3 | | 6x-3=18x | | -12-9= | | 6x-3=23x | | -1/5(-1/3)= | | 43+n=-50 |

Equations solver categories